Roses Monitoring System Via Wireless Sensor Network Using Arduino Microcontroller - Hashim, Khairul Ikhwani; Ismail, Muhammad Izzat; Sofian, Hannah (Journal of Computing Technologies and Creative Content, 2016)
Plant monitoring is important to ensure the healthiness of the plant. The right moisture and temperature is crucial for the plant to growth. Roses is one of the plant that needs to be monitored closely, such as the healthiest of the leaves, petals of the roses, moisture of the soil and roses environment temperature. This paper implements an embedded system for rose monitoring. The proposed system consist of two main parts: hardware part and software part. The hardware is equipped with temperature sensor, soil moisture sensor, arduino microcontroller and XBee Wifi Module. XBee Wifi Module will act as an intermediate device to communicate the hardware and software. The hardware components will read the water content in the soil and surrounding temperature then wirelessly transfer the reading to interface from laptop. When the water content level is decrease to certain level the software part will alert and this information will be sent to activate the water pump relay. The proposed system manages to read the water content in the soil and environment temperature. The water pump will be activated when the water content in soil is decrease.